Panel cointegration testing in the presence of a time trend - Bernd Droge; Deniz Dilan Karaman Örsal (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2009)
The purpose of this paper is to propose a new likelihood-based panel cointegration test in the presence of a linear time trend in the data generating process. This new test is an extension of the likelihood ratio (LR) test of Saikkonen & Lütkepohl (2000) for trend-adjusted data to the panel data framework, and is called the panel SL test. The idea is first to take the average of the individual LR (trace) statistics over the cross-sections and then to standardize the test statistic with the appropriate asymptotic moments. Under the null hypothesis, this standardized statistic has a limiting normal distribution as the number of time periods (T) and the number of cross-sections (N) tend to infinity sequentially. In addition to the approximation based on asymptotic moments, a second approximation approach involving the moments from a vector autoregressive process of order one is also introduced. By means of a Monte Carlo study the finite sample size and size-adjusted power properties of the test are investigated. The test presents reasonable size with the increase in T and N, and has high power in small samples.
Keywords: C33; C12; C15; 330; Panel cointegration Test; likelihood ratio; time trend; Monte Carlo study; Panel; Kointegration; Monte-Carlo-Methode; Theorie